Translational Control of COVID-19 and Its Therapeutic Implication - Zhang, Dejiu; Zhu, Lei; Wang, Yin; Li, Peifeng; Gao, Yanyan (Frontiers in Immunology, 2022)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the causative agent of COVID-19, which has broken out worldwide for two years. However, due to the limited treatment, new cases of infection are still on the rise. Therefore, there is an urgent need to understand the basic molecular biology of SARS-CoV-2 in order to control the disease. Virus replication and spread relies on the recruitment of host ribosomes to translate viral messenger RNA (mRNA). In order to ensure the translation of its own mRNA, the virus has developed a variety of strategies to inhibit the translation of the host mRNA, thereby allowing the translation of its own mRNA while blocking the cellular innate immune response. This review provides an overview of the recent research advances on the molecular basis and complexity of SARS-CoV-2 protein translation. We then summarize how this virus inhibits the translation of the host cell to better utilize the translation elements of the host cell to translate its own proteins and promote the replication of the virus. Finally, we analyze how to use translational inhibitors to prevent or improve COVID-19.